Likuiditas dan kebijakan dividen: Analisis moderasi atas investment opportunity set, effective tax rate, dan pertumbuhan perusahaan pada Indeks Jakarta Islamic 30 - Nilam Ayu Rukmana; Anisa Dewi Arismaya (Kurva: Jurnal Ekonomi Manajemen Keuangan dan Bisnis, 2025)
This study examines whether the Investment Opportunity Set (IOS) is associated with dividend policy and whether liquidity moderates that relationship among firms listed in the Jakarta Islamic Index 30 (JII30) for the 2019–2023 period. Using a quantitative design, the population comprises all JII30 firms, and the sample is selected through purposive sampling based on annual report availability and data completeness. Secondary data are drawn from firms' annual reports and analyzed in EViews 12 using panel regression and an interaction term to test the moderating effect of liquidity. The findings indicate that IOS has a positive but statistically insignificant coefficient on dividend policy. The effective tax rate (ETR) shows a negligible negative association with dividend policy.In contrast, firm growth has a positive and significant effect, suggesting that stronger growth firms tend to maintain dividend payments to signal stability and sustain investor confidence. The moderation test rejects liquidity as a moderator, indicating that liquidity does not strengthen or weaken the IOS–dividend policy relationship in this sample. Overall, the results imply that dividend policy in Sharia-compliant equities is more closely linked to growth prospects than to investment opportunities and short-term liquidity conditions.